2017
DOI: 10.1007/s13202-017-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

A 3D numerical model for investigation of hydraulic fracture configuration in multilayered tight sandstone gas reservoirs

Abstract: Multilayered tight sandstone gas reservoirs with low porosity and low permeability are usually developed by two kinds of hydraulic fracturing techniques, including general fracturing (simultaneously fracturing multiple target zones) and separate layer fracturing (sequentially fracturing the target zones from the bottom-up). However, fractures from different target zones are likely to communicate in the fracturing process which detrimentally causes the waste of fracturing fluid and proppants and finally affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Based on the method and model of Rungamornrat et al (2005) it was found that the expansion of weakly singular symmetric Galerkin boundary elements can simultaneously realise the propagation of multiple 3D fractures in a single horizontal well. The propagation process of multiple hydraulic fractures was simulated using a 3D finite element model (Castonguay et al, 2013;Gao et al, 2018;Gupta and Duarte, 2014). In addition, the shale gas reservoir in the fracture propagation is a moving boundary problem, which makes the application of traditional finite element simulation more complicated and tedious (Guo et al, 2015).…”
Section: Continuum-discontinuum Numerical Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the method and model of Rungamornrat et al (2005) it was found that the expansion of weakly singular symmetric Galerkin boundary elements can simultaneously realise the propagation of multiple 3D fractures in a single horizontal well. The propagation process of multiple hydraulic fractures was simulated using a 3D finite element model (Castonguay et al, 2013;Gao et al, 2018;Gupta and Duarte, 2014). In addition, the shale gas reservoir in the fracture propagation is a moving boundary problem, which makes the application of traditional finite element simulation more complicated and tedious (Guo et al, 2015).…”
Section: Continuum-discontinuum Numerical Methods and Modelsmentioning
confidence: 99%
“…The propagation process of multiple hydraulic fractures was simulated using a 3D finite element model (Castonguay et al. , 2013; Gao et al. , 2018; Gupta and Duarte, 2014).…”
Section: Numerical Analysis Of Continuous Stress Field and Discontinu...mentioning
confidence: 99%
“…Gao et al, 2017 built a 3D finite element model to simulate the propagation of multiple hydraulic fractures in a wellbore to a tight reservoir. In addition, they analyzed and compared the effects of different fracturing techniques and formation properties on fracture morphology [8]. Li et al 2019 used the numerical simulator RFPA-Petrol (Rock-Failure-Process-Analysis on Petroleum-problems) linked hydraulic-mechanical-damage (HMD) model to investigate fracture paths.…”
Section: Introductionmentioning
confidence: 99%
“…Parvizi et al (2015) [17] evaluated the hydraulic fracturing performance in tight sandstone gas reservoirs with high perm streaks and natural fractures and optimized the fracture design parameters and well spacing. Gao et al (2018) [18] developed a 3D numerical model for the investigation of the hydraulic fracture configuration in multi-layered tight sandstone gas reservoirs and compared the effects of general fracturing and separate layer fracturing on the fracture geometry and production performance. Wang et al (2020) [19] presented a thermal-hydraulic-mechanical numerical simulator for the simulation of hydraulic fracturing operations in tight sandstone reservoirs and applied it to a field case in China.…”
Section: Introductionmentioning
confidence: 99%